The place of grape in Turkish folk culture and in context of mythology - Senocak, Ebru (Milli Folklor Dergisi, 2007)
The grape grown since the pre-historic eras has a distinct part within the verbal cultural tradition as well as being an important health source meeting the nutrition need in Turkish folk culture. The grape that was the theme of folk songs, riddles, proverbs, idioms, tales and legends in folk literature was also used with its both curing and symbolic meanings in having a child, marriage and wedding customs, drinking wine, dowry tradition, folk beliefs and folk medicine in our folklore. In the researches carried out depending on the fact that the grape, raw material of wine, is accepted as the drink of the Gods in mythology and it is mentioned in Torah, Bible and the Psalms of David as the sacred drink, it was determined that in Turkish culture and mythology, the grape is the symbol of beauty, fertility, blood, soul, love and health.
Türk halk kültüründe ve mi?toloji?k ba?lamda üzümün yeri?
Keywords: mythology; culture; folk medicine; dream; belief; grape